Robotic system for magnetic resonance imaging-guided focused ultrasound treatment of thyroid nodules - Filippou, Antria; Evripidou, Nikolas; Damianou, Christakis A. (My University, 2023)
Background Herein, a robotic system offering Magnetic Resonance-guided Focused Ultrasound (MRgFUS) therapy of thyroid nodules was developed. Methods The robotic system offers linear motion in 2 PC-controlled axes that navigate a 3 MHz single-element focused transducer. The system, through a C-arm structure attaches to the table of Magnetic Resonance Imaging (MRI) scanners and couples to the neck of patients lying in the supine position. The MRI compatibility of the developed system was assessed inside a 3 T scanner. Benchtop and MRI feasibility studies evaluating the heating performance of the system were executed on excised pork tissue and on homogeneous and thyroid model agar-based phantoms. Results The MRI compatibility of the system was successfully established. Grid sonications executed using robotic motion inflicted discrete and overlapping lesions on the excised tissue, while magnetic resonance (MR) thermometry successfully monitored thermal heating in agar-based phantoms. Conclusions The developed system was found to be efficient with ex-vivo evaluation. The system can perform clinical MRgFUS therapy of thyroid nodules and other shallow targets after further in-vivo evaluation.
Keywords: MRI; MRgFUS; Nodules; Robotic system; Thyroid